Euthanasia and Assisted Suicide: Sweetness in Bitterness - Victoria Ajibola Adeleke (INTERDISCIPLINARY JOURNAL ON LAW, SOCIAL SCIENCES AND HUMANITIES, 2023)
In this paper, a review of the concepts of euthanasia and assisted suicide is conducted. It begins by describing the historical trends from the beginning of the 20th century to the modern-day view. In doing this, some notable cases of these practices in the identified periods are discussed in a separate section. This qualitative study revealed that the doctrine of assisted suicide and the practice of euthanasia differ for different regions. This paper further analysed the argument for and against the doctrine of euthanasia. The theories and the school of thoughts on euthanasia are being examined. The study gives a clue to Nigeria legal perspective on euthanasia. The method of the study adopted was doctrinal in nature with the aid of textbooks, articles and internet sources. The research recommends among others, the improvement of Nigeria Constitution and legislation to promote and protect its citizen’s basic right to human dignity, personal liberty, freedom of thought and right to life as embedded in Chapter IV of the Constitution and to support their health care right. It further notes that there is absolutely no evidence of harms to society or to vulnerable individuals as a result of legalization of assisted suicide and euthanasia, rather than depriving competent adults who want to die sooner their freedom of choice. Keywords: Euthanasia, physician assisted suicide, Human Rights, Medical Ethics